Effects of an additional small group discussion to cognitive achievement and retention in basic principles of bioethics teaching methods (Faculty of Medicine Universitas Indonesia, 2009)
Aim The place of ethics in undergraduate medical curricula is essential but the methods of teaching medical ethics did not show substantial changes. “Basic principles of bioethics” is the best knowledge to develop student’s reasoning analysis in medical ethics In this study, we investigate the effectsof an additional small group discussion in basic principles of bioethics conventional lecture methods to cognitive achievement and retention. This study was a randomized controlled trial with parallel design. Cognitive scores of the basic principles of bioethics as a parameter was measured using basic principles of bioethics (Kaidah Dasar Bioetika, KDB) test. Both groups were attending conventional lectures, then the intervention group got an additional small group discussion. Result Conventional lectures with or without small group discussion significantly increased cognitive achievement of basic principles of bioethics (P= 0.001 and P= 0.000, respectively), and there were significant differences in cognitive achievement and retention between the 2 groups (P= 0.000 and P= 0.000, respectively). Conclusion Additional small group discussion method improved cognitive achievement and retention of basic principles of bioethics. (Med J Indones 2009; 18: 48-52) Keywords: lecture, specification checklist, multiple choice questions